Smash Skill in Table Tennis Games (A Correlational Study of Speed Reaction, Explosive Power of Muscle Arm and Hand-Eye Coordination toward Students' Smash Skills of STOK Binaguna Medan) - Winata, Devi Catur; Syaleh, Muhammad; Munawar, Ahmad Al; Abady, Andi Nur; Keliat, Pedomanta (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
This research is aimed to know the relationship between speed reaction, explosive power of muscle arm, and hand-eye coordination of smash skills of the students of STOK Binaguna Medan. The research method used is a survey method with correlational analysis technique. This study used total sampling, in which all the population was taken as the sample, as the sampling technique. The number of the sample was 35 people. The research shows (1) there is a relationship between speed reaction with smash skill of the students of STOK Binaguna Medan as shown by t obtained = 2.58> t table = 1.70. (2) there is a relationship between explosive power of muscle arm with smash skill of the students of STOK Binaguna Medan, as shown by t obtained = 2.74> t table = 1.70. (3) there is a relationship between hand-eye coordination with smash skill of the students of STOK Binaguna Medan, as shown by t obtained = 3.06> t table = 1.70. (4) there is a relationship between speed reaction, explosive power of muscle arm, and hand-eye coordination toward smash skill of the students of STOK Binaguna Medan, as shown by F obtained = 2.91> F table = 2.91.